VISUALIZATION OF GASEOUS POLLUTANTS THROUGH INTERFEROMETRY - BRODNIANSKÁ, Zuzana; ČERNECKÝ, Jozef (Trends in education, 2008)
In the present contribution the holographic interferometry method of visualisation of gaseous pollutants originating during the burning process is described. The method represents a practical application of theoretical knowledge from the Technical Means of Measuring and Monitoring subject.
Keywords: gaseous pollutants; interferometry; combustion equipment.